2022
DOI: 10.1186/s12884-022-04876-9
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of feelings and experiences associated with perinatal distress during the COVID-19 pandemic

Abstract: Background Rates of perinatal mental health difficulties (experienced during pregnancy and the 12-months postpartum) increased worldwide during the COVID-19 pandemic. In the UK, anxiety and depression were estimated to affect more than half of perinatal women during the first national lockdown. However, little is known about women’s qualitative experiences of distress. This study aimed to extend published quantitative findings resulting from the same data set (Harrison et al., Women Birth xxxx,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…For instance, a multicenter network study reported that 32% of Chinese pregnant women had depression (PHQ-9 ≥ 10) or anxiety (GAD-7 ≥ 5) during the COVID-19 pandemic (39). Jones et al reported that anxiety and depression might have affected more than half of perinatal women during the first national lockdown in England (40). A multi-country network cross-sectional study in Europe reported that 15 and 11% of pregnant women had moderateto-severe depressive symptoms (Edinburgh Depression Scale ≥ 13) and generalized anxiety symptoms (GAD ≥ 10) (26).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a multicenter network study reported that 32% of Chinese pregnant women had depression (PHQ-9 ≥ 10) or anxiety (GAD-7 ≥ 5) during the COVID-19 pandemic (39). Jones et al reported that anxiety and depression might have affected more than half of perinatal women during the first national lockdown in England (40). A multi-country network cross-sectional study in Europe reported that 15 and 11% of pregnant women had moderateto-severe depressive symptoms (Edinburgh Depression Scale ≥ 13) and generalized anxiety symptoms (GAD ≥ 10) (26).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, mothers were not able to rely on family because of distance, 52 and this separation caused distress. 53…”
Section: Discussionmentioning
confidence: 99%
“…Being trauma-informed emphasises the importance of psychological safety, choice and control ( 31 ). Perinatal research conducted in the pandemic illustrates that the pandemic has been a time where people's psychological safety, choice and control have been diminished ( 34 ).…”
Section: Discussionmentioning
confidence: 99%